PEMBELAJARAN STEAM PADA ANAK USIA DINI - Nurul Novitasari.; Nur Aini Zaida; Hasanah . (Universitas Al-Hikmah Indonesia, 2022)
STEAM stimulates children's curiosity and motivation regarding higher-order thinking skills which include problem solving, collaboration, independent learning, project-based learning, challenge-based learning and research, learning activities that are in accordance with the STEAM approach, namely: project based learning. The introduction of STEAM for early childhood can be done by creating a safe and fun learning environment. Providing opportunities for children to explore, discover, build, experiment, predict, seek temporary answers and link knowledge into real life are key activities that can be done in implementing STEAM. These activities can be designed through play activities so that children feel comfortable and enthusiastically involved in them. STEAM learning occurs naturally every day as children explore, play and try new things. When young children have the opportunity to investigate the world around them, they learn and experiment with new STEAM skills and theories. There are several aspects that need to be considered in implementing STEAM for early childhood. These aspects consist of: 1) questioning; 2) exploring and observing; 3) developing skills and processes; 4) communicating; and 5) playing. The steps in the STEM learning approach are as follows: 1) Observer, 2) New Idea, 3) Innovation, 4) Creativity, 5) Society